Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Problem Based Learning pada Pendidikan Pancasila di Kelas VI SDN 02 Tanjung Puan Abai - Gustifal, Rahmi; Putera, Rafhi Febryan; Zainil, Melva; Anita, Yesi (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe how the improvement of student learning outcomes in Pancasila Education learning using the Problem Based Learning (PBL) model in the sixth grade of SDN 02 Tanjung Puan Abai. This research is a Classroom Action Research (CAR) using qualitative and quantitative approaches, conducted in two cycles, namely cycle I (two meetings) and cycle II (one meeting), carried out in four stages: planning, implementation, observation, and reflection. The subjects of this study are the teacher and the sixth-grade students of SDN 02 Tanjung Puan Abai, totaling 22 students, consisting of 12 boys and 10 girls. The results of this study show an improvement in the teaching module in cycle I with an average of 85.84% (B) and in cycle II with 96.42% (SB). The assessment of teacher activity in cycle I had an average of 78.70% (C) and in cycle II 96.42% (SB). The assessment of student activity in cycle I had an average of 78.70% (sufficient) and in cycle II 96.42% (SB). The assessment of students' improvement in learning outcomes in cycle I was 71.21% and in cycle II with an average of 87.88%. Based on these results, it can be concluded that the Problem Based Learning (PBL) model can improve the learning outcomes of Pancasila Education in the sixth grade.